Catalyst-free bottom-up growth of graphene nanofeatures along with molecular templates on dielectric substrates. Issue 38 (21st September 2016) - Min, Misook; Seo, Sohyeon; Yoon, Yeoheung; Cho, Kyungjune; Lee, Sae Mi; Lee, Takhee; Lee, Hyoyoung
Abstract : We synthesized graphene nanoribbons (GNRs) and nanoporous sheets without metal catalysts on a dielectric substrate via molecular, thin film-assisted, bottom-up growth. Abstract : Synthesis of graphene nanostructures has been investigated to provide outstanding properties for various applications. Herein, we report molecular thin film-assisted growth of graphene into nanofeatures such as nanoribbons and nanoporous sheets along with a predetermined molecular orientation on dielectric substrates without metal catalysts. A Langmuir–Blodgett (LB) method was used for the formation of the molecularly patterned SiO2 substrates with ferric stearate layers, which acted as a template for the directional growth of the polypyrrole graphene precursor. The nanofeatures of the graphene were determined by the number of ferric stearate layers ( e.g., nanoribbons from multiple layers and nanoporous sheets from a single layer). The graphene nanoribbons (GNRs) containing pyrrolic N enriched edges exhibited a p-type semiconducting behavior, whereas the nanoporous graphene sheets containing inhomogeneous pores and graphitic N enriched basal planes exhibited the typical electronic transport of nitrogen-doped graphene. Our approaches provide two central methods for graphene synthesis such as bottom-up and direct processes for the future development of graphene nanoelectronics.